HUMAN RIGHTS RELATIONSHIPS ON THOSE CHILDREN STUDIED IN A SCHOOL UNDER ARTICLE 31 OF EDUCATION OF THE CONSTITUTION OF THE REPUBLIC OF INDONESIA 1945 (at Tunas Mulia Elementary School Gading Serpong) - Khairunnisa Khairunnisa; Dewi Ulfah Arini; Tahta Anandea (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The study aims to identify obstacles - obstacles faced in fulfilling a child's basic human rights (human rights) in education article 31. The protection of human rights became an element of legal sovereignty. A legal requirement is good if it produces a good application. The theory supporting this study is the concept of legal sovereignty, where the theory of justice lies in the two principal principles used in creating justice. Same freedom, as long as it benefits all parties, the principle of inequality used to profit the weakest. The research method used is a correlation description analysis with data collection techniques in-depth interviews, observation, and documentation. Studies show that human rights in children have a correlation value of 0.145. Basically, human rights enforcement efforts in basic have a significantly low correlation with Article 31 Education guarantee freedom in self-development in accordance with a nine-year government program.